Nanoindentation study of the creep behavior in a Fe-based bulk metallic glass. (13th November 2017) - Liao, G K; Long, Z L; Zhao, M S Z; Peng, L; Chai, W; Xu, X J; Ping, Z H; Zhang, Y; Yan, C P
Abstract: In this paper, the creep behavior of a Fe-based bulk metallic glass (BMG) was studied by using the nanoindentation testing. According to the microstructural evolution in BMGs, the generalized Kelvin model was employed to describe the creep behavior of this BMG, and a method of separating the viscoelastic and viscoplastic deformation from the indentation creep was proposed. The creep behaviors at various loading rates were systematically analyzed. The obtained results indicated that the viscoelastic or viscoplastic characteristics of Fe-based BMG exhibited a strong dependency on the loading rate. Moreover, the volume of shear transformation zone (STZ) during the creep of Fe-based BMG has also been calculated to further explore its creep mechanism.